Теоретичні основи аналізу зовнішньоекономічної діяльності митними органами - Яковенко, О. В.; Yakovenko, O. (КНТУ, 2015)
У статті сформовано ключові теоретичні положення аналізу зовнішньоекономічної діяльності (ЗЕД) суб’єктів господарювання митними органами. Визначено мету аналізу ЗЕД митними органами, що полягає у всебічному вивченні господарської діяльності суб’єкта ЗЕД для виявлення та запобігання порушенням вітчизняного законодавства у сфері митної справи На основі уточнення мети аналізу виділено завдання, які полягають у перевірці правильності, законності та правомірності, безпечності окремої операції чи ЗЕД вцілому. Окрім того визначено об’єкт, предмет та функції аналізу ЗЕД митними органами. The aim of the paper is the formulation of the main provisions of the customs authorities of foreign economic activity analysis according to the functions assigned to them by the state. The paper presents the key theoretical principles of analysis of foreign entities customs authorities. The purpose of this analysis is a comprehensive study of the economic activity of economic operators to detect and prevent violations of national legislation in the field of customs. The task of this analysis arising from the customs legislation and consist in verifying the correctness, legality and legitimacy, safety or foreign economic activity separate process in general etc.
The Theoretical Basis of Analysis of Foreign Economic Activity by Customs Authorities
Keywords: аналіз ЗЕД; митні органи; предмет аналізу ЗЕД; об’єкт аналізу ЗЕД; функції аналізу ЗЕД; analysis of foreign economic activity; customs authorities; object of foreign economic activity analysis; foreign economic activity analysis functions